The utilisation of Activated Carbon (AC) from palm shell waste to treat textile wastewater - Abdul Kadir, Aeslina; Puade, Azi Zatika (AENSI Publishing Corporation, 2012)
Heavy metals are widely used in textile industries and significant losses occur during the manufacturing and processing of textiles, and these lost heavy metals are eventually discharged in the effluent. Activated carbon (AC) is preferred adsorbent for removal of pollutants from aqueous and liquid phase. In this study, adsorbent fiom palm kernel shell (PSAC), an agricultural waste product were used to remove selected heavy metals which are copper, iron and zinc from textile wastewater. To investigate the effectiveness of palm shell activated carbon in removing heavy metals in textile wastewater, three reactors have been used for textile wastewater treatment. Reactor A treats textile wastewater using commercial activated carbon (F'AC), Reactor B treats textile wastewater using activated carbon from palm shell (PSAC), while Reactor C acts as a control. The three reactors were tested against time with textile wastewater samples taken hm a textile factory, RAMATEX Industries. The effectiveness of both activated carbon was obtained from the quality of effluent. The laboratory assay revealed that Reactor B was found to be better than Reactor A in removing all selected parameters. Reactor B had achieved 17.2% copper removal, 99% iron removal, and 50% zinc removal thus proving its ability to adsorb heavy metals more economically. Therefore it is concluded that PSAC have a potential to be an alternative low cost adsorbent to replace the conventional AC by optimizing the activation procedures, considering the contaminants to be removed.